Interaction design of secure authentication and transaction signing in online banking - Dondana, Marco (My University, 2013)
The presented report documents a research conducted together with the digital security company Gemalto as my Master’s thesis in Interaction Design and Technologies. The focus of the research is the optimal usability of a secure e-banking system with focus on secure authentication and transaction signing use cases. The analyzed scenario features a web interface run on different devices such as laptops and tablets together with an external device designed to face “challenge/response” security solutions called “token”. After considering previous researches in this field and analyzing the boundaries and the specific parameters of the scenario, an analysis of the system currently provided by the company will lead to the first concept ideas. From these concept ideas, a first working prototype will be developed and a usability study will be conducted on it to define the improvements that will conduct to the development of a second version. By comparing the results of the different usability study iterations, a list of design guidelines will be defined as a final result of the research.
Keywords: Interaktionsteknik; Interaction Technologies